INSTRUCTIONAL LEADERSHIP AND TEACHER PERFORMANCE IN CAMBODIAN HIGH SCHOOLS: A MIXED-METHODS ANALYSIS - San Soeurn (jfpublisher, 2025)
Effective educational leadership is critical for improving teacher performance, yet limited empirical evidence exists regarding how leadership practices influence teaching effectiveness in Cambodia's evolving education system. This mixed-methods study examines the relationship between educational leadership practices and teacher performance in ten high schools across Phnom Penh, Cambodia. Data were collected from 286 participants (158 valid survey responses) including school directors, deputy directors, teachers, and students using surveys, semi-structured interviews, and focus group discussions. Findings reveal that while 78% of schools implement professional development activities and democratic leadership is preferred (41.5%), significant implementation gaps persist: 53.1% of teachers report inadequate leadership support, 45% indicate misalignment between professional development and their actual needs, and 46.2% experience insufficient follow-up after training. Public schools show more consistent patterns of low support (52.5%) compared to polarized experiences in private institutions. Teachers participating in mentoring programs report substantial improvements (62%), and 68% note enhanced student motivation following professional development. The study demonstrates that leadership effectiveness depends not on professional development quantity but on quality, relevance, and sustained implementation support. These findings extend educational leadership theory by providing context-specific evidence from Southeast Asia and offer actionable recommendations for strengthening leadership capacity and teacher development systems in Cambodia and similar developing contexts.